Study on caprine hard tick fauna and seasonal variations of tick population in West Azarbaijan province - S Rasouli; M Sadagian; K Jafari; E Valizadeh; M Mojarad (Āsīb/shināsī-i Darmāngāhī-i Dāmpizishkī, 2010)
In order to determine the tick specie of goats, reared in cities of west-Azarbaijan province, the present investigation was performed from March 2006 (Farvardin 1385) to April 2007 (Esfand 1385). Meanwhile, distribution of ticks according to age and sex on different part of the body and the seasonal variation of tick population and infestation were also studied. Overall 1800 goats of both sexes, from 21 cities and their suburbs in west-Azarbaijan province were examined for tick infestation. The results revealed 52 (2.88%) goats were infested by hard ticks. The highest percentage of infestation was observed in Miandoab area during June 2006 (Khordad1385), while the lowest percentage was in Shahindegh area during February 2006. There was a significant difference (p